Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Citra Merek Terhadap Minat Beli di Mixue Kelapa Dua Depok - Alfa Rifzqi, Salman; Cyasmoro, Verry (ARKA INSTITUTE, 2023)
The Purpose of this study was to examine the effect of product quality, service quality, and brand image on purchase intention at Mixue Kelapa Dua Depok with quantitative methods. This data was obtained by randomly distributing to 100 respondents at the Mixue Kelapa Dua Depok Outlet and by accidental sampling technique. This study applies multiple linear regression analysis methods including validity test, reliablity test, classic assumption test, coefficient of determination test (Rsquare), and hypothesis testing with the F test and t test. The result of the study stated that product quality, service quality, and brand image had a positive and significant effect on purchase intention at Mixue Kelapa Dua. The conclusion of this study shows that the Mixue Kelapa Dua outlet has a strong brand image for consumers in terms of product quality, and service quality so that it influences purchase intention, consumer can also give a good assessment of the Mixue Kelapa Dua Depok outlet.